A Geografia Escolar na Província de Minas Gerais no período de 1854 a 1889 - Eduardo Jose Pereira Maia (2014)
The present work aims at understanding the history of School Geography in Minas Gerais province between 1854 and 1889. This is an analysis of the schooling process of Minas Gerais Geography and, hence, Brazilian Geography during the second half of the nineteenth century. We claim that the teaching of Geography was not restricted to Pedro II School and its creating process was not the simple extension of academic and scientific knowledge. On the contrary, it was a slow process of disciplinarization, in which the textbook authors and primary, secondary and normal schools teachers played a key role. We also aim at analyzing the goals of Geography teaching beyond the manuals prescription; our research combined the prescription analysis and daily practices. Our main sources, in addition to legislation, were school programs, reports of the education board, tests and exams, minutes and reports gathered in Minas Gerais Public Archive (APM); Geography and Chorography textbooks, examined in collections of the Library of Textbooks in the Faculty of Education of the University of São Paulo (BLD / FEUSP), National Library (BN), State Library of Minas Gerais, and the Digital Library of the Federal Senate; the Center for Memory of Pedro II School (NUDOM); and other documents on the Brazilian Schoolbooks Database (LIVRES). The content relating to Brazilian and Minas Gerais province Geography comprised an expressive portion of tests and examinations. This showed the importance of the knowledge of the national territory in the period. The significant number of textbooks written by Brazilian authors circulating in the Empire during the second half of the nineteenth century pointed out that there was a national production of knowledge in the field, contradicting old assumptions that Geography teaching in Brazil was exclusively produced by foreign authors.